ANALISIS MODEL PEMBELAJARAN PROJECT BASED LEARNING DI SMA NEGERI 1 TONDANO - Kabahing, Misi Julia; Wuisang, Jerry; Oroh, Silvana; Makaliwe, Niny (Literacy: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze how to analyze the Implementation of the Project Based Learning learning model in SMA Negeri 1 Tondano in order to improve the quality of the learning process and student learning outcomes. This Project Based Learning learning model is a student-centered learning, focused on problems, meaningful learning units by combining concepts from a number of components, both Knowledge and disciplines. This study used a qualitative approach to overcome a research problem whose variables are not yet known and need to be explored in depth. Data collection using observation, interview, and Documentation techniques, then the data was analyzed. The results of the study found that the Implementation of the Project Based Learning learning model in SMA Negeri 1 Tondano significantly increased student learning creativity and Changes in student attitudes in learning. Keywords : Learning Model Analysis, Project Based Learning